A prospective, observational grouped analysis to evaluate the effect of triptorelin on lower urinary tract symptoms in patients with advanced prostate cancer. (June 2015) - Gil, Thierry; Aoun, Fouad; Cabri, Patrick; Maisonobe, Pascal; van Velthoven, Roland
Objectives: Few studies have assessed the effect of gonadotropin-releasing hormone (GnRH) agonists, such as triptorelin, on lower urinary tract symptoms (LUTS) in patients with advanced prostate cancer. Therefore, multiple, national observational, noninterventional studies were initiated to assess the effectiveness of triptorelin in reducing moderate or severe LUTS [International Prostate Symptom Score (IPSS) >7] in men with prostate cancer starting triptorelin therapy in clinical practice. Methods: Prospective, noninterventional, multicentre studies of LUTS located in Algeria, Belgium, China, Hungary, Romania and South Korea, in patients who were scheduled to receive triptorelin (3-month extended release or 1-month formulation) in clinical practice. The primary effectiveness endpoint was the proportion of patients with moderate or severe LUTS after 48 weeks as assessed by IPSS. Secondary endpoints included the distribution of IPSS categories, total IPSS and prostate-specific antigen (PSA) levels at baseline, 24 and 48 weeks. Results: In total, 2461 patients were recruited in the studies; 1282 patients had moderate or severe LUTS at baseline (IPSS > 7), received triptorelin and had follow-up IPSS. Mean total IPSS was reduced from 18.2 [95% confidence interval (CI) 17.8–18.5] at baseline to 11.9 (95% CI 11.5–12.3; p < 0.001) and 10.6 (95% CI 10.2–11.0; p < 0.001) at weeks 24 and 48, respectively. Mean PSA levels were reduced from 117.9 ng/ml (95% CI 93.8–141.9) at baseline to 8.5 ng/ml (95% CI 5.2–11.7) and 16.6 ng/ml (95% CI 7.4–25.8) at weeks 24 and 48, respectively. There was a significant correlation between total IPSS change from baseline and PSA change from baseline at weeks 24 and 48 (ρ = 0.3 and 0.2, p < 0.001). Conclusions: The improvement in LUTS in men with locally advanced or metastatic prostate cancer after 24–48 weeks suggests that triptorelin is effective in improving LUTS in this subgroup of patients.